1994
DOI: 10.5089/9781451855531.001
|View full text |Cite
|
Sign up to set email alerts
|

Fixed or Floating Exchange Regimes: Does it Matter for Inflation?

Abstract: This is a Working Paper and the author would welcome any comments on the present text. Citations should refer to a Working Paper of the International Monetary Fund, mentioning the author, and the date of issuance. The views expressed are those of the author and do not necessarily represent those of the Fund.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 17 publications
0
10
1
Order By: Relevance
“…Ghosh et al (1997) find that both the level and variability of inflation are substantially lower under fixed exchange rates than under flexible rates. Their results are contradictory to the conclusion of Quirk (1994), which asserts there is not much relationship between exchange rate regime and inflation behavior. In general, it is quite uncontroversial to state that the insulation property of the flexible exchange rate regime is imperfect (Corden, 1985;Mussa, 1979;Salant, 1977).…”
Section: Introductioncontrasting
confidence: 55%
“…Ghosh et al (1997) find that both the level and variability of inflation are substantially lower under fixed exchange rates than under flexible rates. Their results are contradictory to the conclusion of Quirk (1994), which asserts there is not much relationship between exchange rate regime and inflation behavior. In general, it is quite uncontroversial to state that the insulation property of the flexible exchange rate regime is imperfect (Corden, 1985;Mussa, 1979;Salant, 1977).…”
Section: Introductioncontrasting
confidence: 55%
“…Effective exchange rates were used recently as a more appropriate measure of the degree of devaluation in less developed countries (LDCs) (e.g. Overall, as Quirk (1994) observed, differences between the various exchange rate regimes have narrowed, once adjustments in the case of fixed exchange rate regimes are taken into account. Bahmani-Oskooee and Malixi (1992) found that the effective exchange rate has a positive significant effect on inflation in Egypt.…”
Section: Introductionmentioning
confidence: 99%
“…Linkages induced by a fixed exchange rate arrangement can also be gauged by, say, interactions between inflation (Cheung and Yuen, 2002;Ghosh et al, 1997;Quirk, 1994 Apparently, both theoretical and empirical results are ambivalent on the issue. There is not a definite verdict that the prescription of RMB flexibility will give China an independent monetary policy.…”
mentioning
confidence: 99%